Exposure to dipeptidyl‐peptidase 4 inhibitors and the risk of pneumonia among people with type 2 diabetes: Retrospective cohort study and meta‐analysis. Issue 10 (25th August 2020) - Morieri, Mario Luca; Bonora, Benedetta Maria; Longato, Enrico; Di Camilo, Barbara; Sparacino, Giovanni; Tramontan, Lara; Avogaro, Angelo; Fadini, Gian Paolo
Abstract: Aim: Concerns have been raised that dipeptidyl‐peptidase 4 inhibitors (DPP‐4i) may increase the risk of pneumonia. We analysed observational data and clinical trials to explore whether use of DPP‐4i modifies the risk of pneumonia. Methods: We identified patients with diabetes in the Veneto region administrative database and performed propensity score matching between new users of DPP‐4 inhibitors and new users of other oral glucose‐lowering medications (OGLMs). We compared the rate of hospitalization for pneumonia between matched cohorts using the Cox proportional hazard model. The same analysis was repeated using the database of a local diabetes outpatient clinic. We retrieved similar observational studies from the literature to perform a meta‐analysis. Results from trials reporting pneumonia rates among patients randomized to DPP‐4 inhibitors versus placebo/active comparators were also meta‐analysed. Results: In the regional database, after matching 6495 patients/group, new users of DPP‐4 inhibitors had a lower rate of hospitalization for pneumonia than new users of other OGLMs (HR 0.76; 95% CI 0.61‐0.95). In the outpatient database, after matching 867 patients/group, new users of DPP‐4 inhibitors showed a non‐significantly lower rate of hospitalization for pneumonia (HR 0.65; 95% CI 0.41‐1.04). The meta‐analysis of observational studies yielded an overall non‐significant lower risk of hospitalization for pneumonia among DPP‐4 inhibitor users (RR 0.81; 95% CI 0.65‐1.01). The meta‐analysis of randomized controlled trials showed no overall effect of DPP‐4 inhibitors on pneumonia risk (RR 1.06; 95% CI 0.93‐1.20). Conclusion: The use of DPP‐4 inhibitors can be considered as safe with regard to the risk of pneumonia.